Combination of Periodontal and Aesthetic Surgery in Cases of Periodontal Tissue Abnormalities - Hartanti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: A high superior labial frenulum causes a gap in the incisors and in the long term will lead to periodontal disease such as gingival enlargement. And pigmentation abnormalities that usually appear physiologically on the gingiva which disturb the aesthetic aspect of the patient. Anatomical abnormalities and abnormalities that occur due to periodontal disease if not treated will result in the severity of periodontal disease progression. Case: A 20-year-old female patient complained of enlargement of her gums and the color of her gums was slightly dark. Case Management: Intra oral examination revealed a high frenulum, gingival enlargement and gingival pigmentation. Discussion: Surgical procedures performed at one visit to overcome the patient's problem, periodontal surgery was performed in the form of gingivektomi, frenectomy and for aesthetic surgery in the form of gingival depigmentation in sequence with a surgical blade. Conclusion: Conventional surgical procedures in this case can be performed with sequential stages in one visit for the efficiency of patient visits and time. So that patients are more comfortable without having to repeat periodontal surgery.